From bedside to bug side: clinical, haematological and genetic markers of antibiotic-resistant bacterial isolates from children admitted with sepsis in Kaduna State, Nigeria – a protocol for a cross-sectional study - Livingstone Gayus Dogara; Sani Musa; David W Cleary; Shamsudin Aliyu; Nuruddeen Bida Abdullahi; Hajara Lawal Khalid; Sadiq Kwaifa Salihu; Aliyu Umar Dahiru; Amal Aminu Muhammad; Kamilah Abdullahi; Suleiman Salisu; Summaiyah Ahmad Gumbi; et al. (BMJ Open, 2025)
Introduction Sepsis and antibiotic resistance constitute a deadly synergy, causing the loss of millions of lives across the world, with their economic and developmental consequences posing a threat to global prosperity. Their impact is disproportionately felt in resource-limited settings and among vulnerable populations, especially children. A key challenge is prompt diagnosis and timely commencement of appropriate antibiotic therapies. These challenges are compounded in low-income and middle-income countries by a lack of comprehensive epidemiological data, with Nigeria being one such country for which it is lacking. Kaduna is the third largest state in Nigeria, with over 10 million inhabitants, of whom more than half are children under 14 years old. While bacterial sepsis and antimicrobial resistance (AMR) are recognised as a growing problem in the state, there are huge gaps in the current understanding of their aetiology. This project employs a cross-sectional design to investigate the clinical and haematological markers of paediatric sepsis, alongside determining the bacterial cause and prevalence of AMR at four high-turnover hospitals in Kaduna State, Nigeria. Further, whole-genome sequencing of isolated bacterial pathogens will be performed to determine the genetic features of resistance. This project represents the largest surveillance study of paediatric sepsis in Kaduna to date. Additionally, we aim to use the clinical, haematological, microbiological and genomic data to derive predictive models for sepsis causes, treatment strategies and patient outcomes.Methods and analysis This is a hospital-based, cross-sectional study that will recruit up to 461 children with bacterial sepsis who were admitted at the two teaching and two general hospitals in Kaduna State, Nigeria. Children presenting with features of fever, subnormal temperature and body weakness would be recruited into the study and have their blood samples collected. The blood samples will be used for culture, complete blood count, HIV and malaria testing. Accordingly, we will capture clinical presentation, haematological characteristics, causative pathogen from blood culture and patient outcomes. Nutritional status, known congenital immunosuppressive diseases, HIV infection and malaria infection will also be determined and documented. The bacterial isolates will be phenotypically characterised for AMR and genotypically following whole genome sequencing. Known and potential confounders to the outcomes of bacterial sepsis would be assessed in all participants, and adjustment for confounding would be performed using logistic regression and/or stratification±Mantel-Haenszel estimator where applicable.Ethics and dissemination Ethical approvals were granted by the University of Birmingham (ERN_2115-Jun2024), the Ahmadu Bello University Teaching Hospital (ABUTHZ/HREC/H45/2023), Barau Dikko Teaching Hospital, Kaduna (NHREC/30/11/21A) and the Kaduna State Ministry of Health (MOH/AD M/744/VOL.1/1110018). The study will be conducted using the international guidelines for good clinical practice and based on the principles of the Declaration of Helsinki. The results will be disseminated via oral and poster presentations in scientific conferences and published in peer-reviewed journal articles.